Phosphotyrosine confers client specificity to Hsp90 - Mayer, Matthias P. (Molecular cell, 2010)
In this issue of Molecular Cell, Mollapour et al. (2010) report a new tyrosine phosphorylation site in Hsp90, which is essential for Hsp90's interaction with a subset of its client proteins, notably protein kinases.